Report on professional attachment with Sony International (Singapore) Ltd. - Ong, Terence Swee Sin. (2009)
My professional attachment with Sony International (Singapore) Ltd [SONIS] has ended. This report is a documentation of the 8 weeks' stay with the company. It highlights learning encounters as well as attempts to translate some intangible aspects of my experience into writing.